De Novo Venom-Gland Transcriptomics of Spine-Bellied Sea Snake (Hydrophis curtus) from Penang, Malaysia—Next-Generation Sequencing, Functional Annotation and Toxinological Correlation - Choo Hock Tan; Kae Yi Tan (Toxins, 2021)
Envenomation resulted from sea snake bite is a highly lethal health hazard in Southeast Asia. Although commonly caused by sea snakes of Hydrophiinae, each species is evolutionarily distinct and thus, unveiling the toxin gene diversity within individual species is important. Applying next-generation sequencing, this study investigated the venom-gland transcriptome of Hydrophis curtus (spine-bellied sea snake) from Penang, West Malaysia. The transcriptome was de novo assembled, followed by gene annotation and sequence analyses. Transcripts with toxin annotation were only 96 in number but highly expressed, constituting 48.18% of total FPKM in the overall transcriptome. Of the 21 toxin families, three-finger toxins (3FTX) were the most abundantly expressed and functionally diverse, followed by phospholipases A2. Lh_FTX001 (short neurotoxin) and Lh_FTX013 (long neurotoxin) were the most dominant 3FTXs expressed, consistent with the pathophysiology of envenomation. Lh_FTX001 and Lh_FTX013 were variable in amino acid compositions and predicted epitopes, while Lh_FTX001 showed high sequence similarity with the short neurotoxin from Hydrophis schistosus, supporting cross-neutralization effect of Sea Snake Antivenom. Other toxins of low gene expression, for example, snake venom metalloproteinases and L-amino acid oxidases not commonly studied in sea snake venom were also identified, enriching the knowledgebase of sea snake toxins for future study.